Similarity Segmentation Approach For Sensor-Based Human Activity Recognition - Baraka, Abdulrahman M. A. (2024)
The researchers attempted to enhance the segmentation method by proposing various techniques. However, most of them focus on each window’s features, and few consider the temporal relationships between the adjacent windows. Therefore, an analysis of the impact of window size on the performance of basic and transitional activity recognition is performed using a deep learning model.